Occlusal Analysis and Management of a Patient with Unilateral High-Frequency Hearing Impairment and Stiff Shoulder: A Case Report - Torii, Kengo (British Journal of Healthcare and Medical Research, 2022)
Although the relationship between low-frequency hearing loss and dental occlusion has been reported, the treatment of high-frequency hearing impairment using occlusal position correcting therapy has not yet been reported. As a result of the occlusal analysis of a woman who was pointed out as having a high-frequency hearing impairment (4000Hz: 40dB) in the right ear at the complete medical checkup, it was found that there was no occlusal contact at all except for the left premolars and molars. The occlusal force on the right side was mean 5.3 kg, and the left side was mean 14.0 kg. The statistical difference between the mean values was significant (p<0.01). As a result of improving the occlusion, the left and right premolars and molars were evenly in contact. The occlusal force was improved mean 10.0 kg on the right side, mean 12.0 kg on the left side respectively (not significant). High-frequency hearing impairment disappeared (400Hz: 20dB). Since the right molars are not in occlusion, the masticatory muscles are not capable of isometric contraction and the bite force is weak. Since the tensor tympani is also innervated by the same mandibular nerve as the masticatory muscle, it is thought that the contracting force of the tensor tympani is also weakened, resulted in high-frequency hearing impairment occurred.